2015
DOI: 10.1109/tap.2014.2365828
|View full text |Cite
|
Sign up to set email alerts
|

A Printed Triangular Monopole With Wideband Circular Polarization

Abstract: Abstract-A printed triangular monopole antenna with wideband circular polarization is presented. The wideband circular polarization is achieved by asymmetrical excitation of a triangular ground plane and planar triangular monopole. The combined radiation provides a wide axial-ratio bandwidth spanning from 1.42 to 2.7 GHz (62%). A parametric study of key geometric parameters is given for clear understanding of the radiation mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…After bending the quasi‐transmission line with lower impedance ( Z 2 ), the case is denoted as Bent Monopole. For the conventional monopole antenna with the symmetrical feeding structure, the two horizontal current densities along the edge of the ground plane are mutually cancelled . The resonance is controlled by the guided length of the monopole.…”
Section: Antenna Designmentioning
confidence: 99%
See 1 more Smart Citation
“…After bending the quasi‐transmission line with lower impedance ( Z 2 ), the case is denoted as Bent Monopole. For the conventional monopole antenna with the symmetrical feeding structure, the two horizontal current densities along the edge of the ground plane are mutually cancelled . The resonance is controlled by the guided length of the monopole.…”
Section: Antenna Designmentioning
confidence: 99%
“…Because of its low profile, light weight, miniaturized size, easy impedance matching performance, and wide impedance bandwidth, the microstrip monopole antenna has attracted considerable interest for applications in the wireless communication. To enhance the antenna performance, such as impedance bandwidth, sized reduction, and circular polarization, many research studies have been presented . In 2004, a two‐finger monopole antenna was developed by Chen et al The dual‐band performance is shown and easily tuned by changing the finger length, individually.…”
Section: Introductionmentioning
confidence: 99%
“…By etching an inverted U‐shaped strip and an open‐loop design in the ground plane, the 3‐dB AR‐BW was enhanced up to 62% and 65.2%, respectively. Apart from these techniques, the CP bandwidth can also be improved using asymmetrically fed monopole antennas . In the recent literature, an L‐shaped radiator with broadband and unidirectional CP radiation was reported for array applications and a C‐shaped radiator with a modified ground plane in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A novel compact UWB printed slot antenna having three extra bands for many wireless applications is shown in [11]. A printed triangular monopole antenna having wideband circular polarization is represented [12]. The wideband circular polarization is attained through asymmetrical excitation of a triangular ground plane in addition to planar triangular monopole represented in [12].…”
mentioning
confidence: 99%
“…A printed triangular monopole antenna having wideband circular polarization is represented [12]. The wideband circular polarization is attained through asymmetrical excitation of a triangular ground plane in addition to planar triangular monopole represented in [12]. A novel technique to develop the axial ratio (AR) of circularly polarized patch antenna is shown in [13].…”
mentioning
confidence: 99%